FGFR3 and Cyclin D3 as urine biomarkers of bladder cancer recurrence. (March 2016) - Blanca, Ana; Requena, Maria J; Alvarez, Jose; Cheng, Liang; Montironi, Rodolfo; Raspollini, Maria R; Reymundo, Carlos; Lopez-Beltran, Antonio
Aim : To assess the diagnostic performance of FGFR3 and Cyclin D3 urinary protein levels in detecting bladder cancer recurrence.Patients & methods: Urine of 321 patients in follow-up for bladder cancer and 150 non-neoplastic urine controls was included. Cytology, cystoscopy and FGFR3 and Cyclin D3 expression by western blot were performed.Results: One hundred ten (34.3%) patients had evidence of tumor recurrence. The sensitivity and specificity of cytology/cystoscopy was 80 and 84%, and for FGFR3/Cyclin D3 was of 73 and 90%.Conclusion: Combined urinary FGFR3/Cyclin D3 expression shows improved detection rates for bladder cancer recurrence with high specificity and sensitivity, and within the same range of detection shown by cystoscopy, therefore supporting its potential use as noninvasive diagnostic biomarker for bladder cancer recurrence.